Features of Arthrosis of the Shoulder Joint in the Conditions of Initially Realized Shoulder Instability and in Case of its Combination with Damage to the Rotator Cuff According to Magnetic Resonance Imaging and Arthroscopy - Strafun, S.S.; Kozarenko, T.M.; Nehria, N.M. (TERRA ORTHOPAEDICA, 2021)
Relevance. Osteoarthritis (OA) leads to functional limitation and reduced quality of life; it is a major cause of pain and disability. Currently, there is a relatively small number of radiological studies concerning the features of OA of the shoulder joint (SJ) provoked by the realized instability and its combination with damage to the tendons of the rotator cuff (RC) of the shoulder. Objective: to study the features of the manifestations and course of SJ OA in the conditions of initially realized isolated instability in combination with damage to the tendons of the RC according to magnetic resonance imaging (MRI) and arthroscopy. Materials and Methods. The MRI and arthroscopy data of 75 patients with isolated Bankart lesion and combination with RC tendon damage were retrospectively analyzed. The results of the MRI examination were independently assessed by 2 radiologists with 8 and 10 years of experience. Arthroscopic diagnosis was performed at the beginning of the reconstructive stage by a standard examination from 21 points. The degree of articular cartilage damage on MRI was determined according to the adapted classification of R. Outerbridge. Results. In Bankart lesion, sites of chondromalacia of the glenoid cavity cartilage can be detected in the form of a linear or curvilinear hyperintensive MR signal on PDfs in the cartilage thickness or as its marginal defect. The thickness of the cartilage in primary dislocations is generally preserved. When instability is combined with RC tendon damage, the degree of cartilage damage is much greater with a decrease in its thickness. The largest area of cartilage damage is observed when 2 or more RC tendons are damaged. Conclusions. Primary SJ dislocation is not always accompanied by damage to the articular cartilage. The MR-semiotics of SJ OA in primary dislocation and in a combination with damage to the tendons of RC has the corresponding features. Delaying the restoration of stability in the shoulder joint with the help of surgical treatment is an unfavorable prognostic factor in the development of rheumatoid arthritis and OA SJ. Realized instability in combination with damage to the rotator cuff is an extremely aggravating prognostic factor for OA, as it adds an additional pathophysiological factor in the form of rotational arthropathy.